The Theories and Studies of the Elite in Soviet of Post-Soviet Society - Matonytė, Irmina (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to analyze the theories and studies of the elites in the Soviet and post-Soviet context. The author grounds the analysis on a view that the studies of political sociology, especially the elitology, depends upon the social context and the political regimes. The author attempts to differentiate the liberal schools in Warsaw and Budapest from the conservative school in Moscow and the periphery of the Soviet Union. She develops her analysis by suggesting that the legacy remains an important part of the practice of scientific enquiry.
Keywords: theories of the elite; political regime; Soviet society; post-Soviet society